Being Cunningham’s Women: The Portrayal of Women in Michael Cunningham’s The Hours - Citra Dewi Saraswati (Passage, 2014)
This present study entitled Being Cunningham’s Women: The Portrayal of Women in Michael Cunningham’s The Hours is aimed to unearth the way in which Michael Cunningham, as a male author, portrays women in the novel The Hours. This study employs qualitative descriptive method coupled with textual analysis approach. It can be seen from the portrayal of women as the ones who are unconfident and exhausted in domestic sphere yet powerful enough to make their own decision to liberate themselves from the exhaustion caused by their life. In other words, Cunningham subverts Gubar’s (1980, cited in Lange, 2008) notion that male authors perceive women as “blank page.” With the benefit of stream of consciousness method, Cunningham has successfully portrayed women’s experience and their situation accurately while, at the same time, diffusing liberal feminism value in his work. Keywords: Feminism, Liberal Feminism, Portrayal, Stream of Consciousness